URGENSI LINGKUNGAN DALAM PROSES PENDIDIKAN ANAK - Yaqien, Nurul (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2009)
In the Islamic school process, environment-role is affecting to the education accomplishment, either in Islamic school or not. Education field out of Islamic school such as; home-schooling and society-schooling. If these could work each other propitiously, so the result would be filled the bill by government, people, and religion. Otherwise, if Islamic education is only focused on classroom-teaching and paying no regard to society education. Thus, very hard to attain intended outcome. Furthermore, if Islamic education does not care about family setting so will occur teaching learning process-failure especially Islamic religion subject. Therefore, in the carrying out of education in Islamic school, the importance of environment setting in education needs serious consideration to figure ideal human by government, people, and religion. In order that Islamic education is not gone over.Â Â Â Keyword: Enviroment, Islamic-Education